Carissa spinarum L.: A Case Study in Ethnobotany and Bioprospecting Research - Sheridan, Helen; Smyth, Ciara (Intech Open, 2022)
This study explores ethnobiological and bioprospecting research through the lens of Carissa spinarum L., using it as a case study to examine wider trends in such research. Hunn’s Phasing in Ethnobiology is used as a framework, analysing the extensive research of a species used in healing, diet and other domains. Most reported studies are illustrative of Phase I Ethnobiological research based on the lack of basic context, emic or ecological detail, or a sense of collaboration with participants or across disciplines. Elements of Phases II, III and IV are evident in some studies highlighting ethnographic context, ecological issues or indigenous knowledge and rights. The extractive character of Phase I research, usually used for bioprospecting purposes, decontextualises plant use and may contribute to the historically poor results from ethno-directed bioprospecting. The widespread marginalisation of the social sciences in bioprospecting research can invalidate the whole research project and in turn ethnomedical plant use itself. A species such as Carissa spinarum L., emerging from Phase I research, can become a mere collection of its phytochemical parts, invalidated if those parts do not meet scientific measures of value. The collaborative character of Phase IV and V Ethnobiology would reward with more ethical and effective research with healing plants.
Medicinal Plants
PUBLISHED
Keywords: Research ethics; Emic; Medicinal plants; Traditional medicine; Hunn phases of ethnobiology; Ethnopharmacology; Ethnomedicine; Case study; Bioprospecting; Carissa spinarum; Identities in Transformation; Immunology, Inflammation & Infection; Inclusive Society; International Development; Ethnobotany; Ethnopharmacology; Herbal Medicine and Ethnopharmacology; Medical Humanities; Traditional Knowledge; Culture; Globalization; Health; Social participation